Biomechanical measures of function of the ano-rectal region of the human body - Alqudah, Maha Mohammed (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2015)
In this research, the Functional Lumen Imaging Probe (FLIP), a novel measurement tool, was adapted to measure the biomechanical properties and morphological changes of the ano-rectal region during distension and provocative manoeuvres. Two customs made FLIP probes (prototype 1& prototype 2) and original EndoFLIP® (prototype 3) were developed and tested in bench top studies and in pilot studies.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin